Synthesis and process parameter optimization of immobilizing CLEA-lipase from fish viscera onto magnetic nanoparticles - Khatun, Hanufa; Yusof, Faridah; Mohamed Azmin, Nor Fadhillah (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
The purpose of this research is to optimize the immobilization of lipase from the viscera of channel catfish to magnetic nanoparticles (MNP-lipase) using CLEA technology, forming a new immobilized enzyme. Lipase was obtained from the viscera of channel catfish, using ammonium sulfate to salt it out. Magnetic nanoparticles were obtained using the co-precipitation method, in which ferric chloride (FeCl3.6H2O) and ferrous sulfate (FeSO4.7H2O) gave the Fe3+ and Fe2+ ions, and precipitation was done by adding ammonium hydroxide which enables the formation of iron oxide magnetic nanoparticles. The functionalized magnetic nanoparticles were immobilized to lipase using the CLEA method, and this immobilization process was optimized. Glutaraldehyde was used as the cross-linker, bovine serum albumin (BSA) was used as a proteic feeder, and acetone as the solvent. One Factor at a Time (OFAT) was used in the process of optimization. The significant factors were considered to be glutaraldehyde, acetone and BSA, and the optimum concentrations of these components were determined to be 80 mM, 60% v/v and 0.18 mM respectively, to produce an optimum new MNP-lipase from the viscera of channel catfish.